A Landscape Study on COVID-19 Immunity at the Single-Cell Level - Wei, Rongguo; Qin, Zheng; Huang, Qi; Liu, Lulu; Cheng, Fang; Meng, Songdong; Wang, Lin (Frontiers in Immunology, 2022)
Since 2019, the coronavirus (COVID-19) has outbroken continuously, spreading internationally and threatening the public health. However, it was unknown that how the disorder at the single-cell level were associated with the pathogenesis of COVID-19. This study presented the disorders of macrophages, epithelial cells, CD8+T cells and NK cells at the single-cell level in the courses of COVID-19, and analyzed the immune response to cytokine storm. Compared with the healthy group, COVID-19 patients had higher proportions of macrophages and lower proportions of T and NK cell, especially proportions of macrophages and epithelial cells with an increase during patients’ conditions from mild to severe. This study suggested that there were high levels of pro-inflammatory and chemo-kine expressions in cells of COVID-19, and analyzed cell subsets to explore its changes and pathways. It was worth noting that several subsets of macrophages, epithelial cells, CD8 T cells and NK cells were involved in inflammation pathways, including TNF signaling pathway and IL-17 signaling pathway. Besides, the pathways interacting COVID-19 and cytokine receptor with each other were remarkably enriched. And these cell subsets played important roles in inflammation, and their abnormal functions may cause COVID-19. In conclusion, this study provided an immune outlook for COVID-19 at the single-cell level and revealed different pathways in immune response of COVID-19 single cells.